Ultrasound appearance and targeted therapy of symptomatic neural lesions in the breast and chest wall after breast cancer surgery - Steyerova, Petra; Zimovjanova, Martina; Lambert, Lukas; Burgetova, Andrea (Medical ultrasonography, 2023)
AIM: To evaluate the feasibility of ultrasound (US) in identification of nerve lesions after breast cancer surgery in patients with neuropathic pain and assess the effect of a targeted US-guided therapy. MATERIAL AND METHODS: Patients with neuropathic pain after breast cancer surgery underwent US examination. Nerve lesions identified by US were treated by a US-guided application of a mixture of local anesthetics and corticoids. The patients reported pain relief on a 100-point scale (0% = no effect, 100% = complete relief) and its duration in the next 18 months. RESULTS: We performed 17 interventions in 11 women. A neuroma was observed in 2 patients, edema of the nerve in 5 patients, and scarring across the nerve in 4 patients. The affected nerves were the intercostobrachial nerve (5 patients), the long thoracic nerve (4), cutaneous branch of the pectoral nerve (1), and both the intercostobrachial and the long thoracic nerve (1). After 15 (88%) interventions, the patients reported relief (55±32%) with a median duration of 3 months (0.5-18 months). CONCLUSION: In patients after breast cancer surgery, ultrasound can reliably identify small painful neural lesions which can be efficiently treated by ultrasound-guided intervention.
Keywords: Mastectomy; Neuralgia; nádory prsu; Thoracic Wall; lidé; Female; neuralgie; hrudní stěna; Breast Neoplasms; nervová blokáda; Nerve Block; ženské pohlaví; mastektomie; Humans